Implementasi Routing Protocol OSPF (Open Shortest Path First) dalam Jaringan SOHO (Informatics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2023)
With a computer network, a computer can be connected to each other either by using the internet or without the internet. To be able to connect with each other there is a data exchange process. The process of sending data is known as routing. OSPF routing is a routing protocol that uses the concept of a routing hierarchy, meaning that OSPF divides the network into several levels. by using the concept of OSPF this router will determine the shortest path to be passed. That way, the process of sending data will be faster to the recipient. The purpose of this research is to build a network that can send messages efficiently. The benefit of this research is being able to build and simulate the OSPF routing protocol in a LAN network using Cisco Packet Tracer version 8.2.0. By using the simulation method, conducting experiments using a model of a system starting from the topology design, IP address mapping, and the configuration process. The results obtained from this research is a topology that is designed and designed to produce a SOHO network that is able to communicate between networks with each other even though they are on different networks and is able to choose the path it takes based on the shortest route.